Pengaruh Rasio Profitabilitas dan Rasio Aktivitas terhadap Harga Saham pada Perusahaan Sub Sektor Ritel di Indonesia - Febrisi Dwita; Nurul Kamila; Adrianus Trigunadi Santosa; Leony Agustine (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
This research was conducted to determine the effect of profitability ratios, namely Gross Profit Margin and Return on Equity and activity ratios, namely Total Asset Turnover and Working Capital Turnover, which have an influence on stock prices of retail companies in Indonesia. In this study, there were 10 retail companies that had been listed on the Indonesia Stock Exchange from 2008 to 2020 using multiple linear regression analysis techniques. The results of this study are that the Gross Profit Margin, Return on Equity and Total Asset Turnover variables have an influence on retail company stock prices while the Working Capital Turnover variable has no effect on retail company stock prices in Indonesia. From the results of this study are expected to provide information about the factors that affect the company's stock price so that investors can invest properly. Keywords: stock prices, activity ratios, profitability ratios